2012
DOI: 10.1007/s00125-011-2443-7
|View full text |Cite
|
Sign up to set email alerts
|

The association between prior infection with five serotypes of Coxsackievirus B and incident type 2 diabetes mellitus in the EPIC-Norfolk study

Abstract: Aims/hypothesis Infections with Coxsackieviruses have been linked to beta cell dysfunction. Given the importance of beta cell dysfunction in the aetiology of type 2 diabetes, we hypothesised that prior infection with Coxsackieviruses B would increase the risk of type 2 diabetes. The aims of the study were to estimate cross-sectional associations between potential predictors of previous infection and seropositivity for Coxsackievirus B serotypes 1-5 (CBV1-5), and then to assess the association between seroposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Some bacterial, viral and parasitic infectious agents are well established causal factors for certain types of cancer 1 or have been linked to the development of inflammatory diseases such as multiple sclerosis 2 , and cardiovascular disease 3,4 . However, much of this evidence is derived from cross-sectional or case-control analyses that are unable to determine temporality, or from small nested case-control studies that have generally been small or have focused on a small number of infectious agents, leading to inconsistent findings 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Some bacterial, viral and parasitic infectious agents are well established causal factors for certain types of cancer 1 or have been linked to the development of inflammatory diseases such as multiple sclerosis 2 , and cardiovascular disease 3,4 . However, much of this evidence is derived from cross-sectional or case-control analyses that are unable to determine temporality, or from small nested case-control studies that have generally been small or have focused on a small number of infectious agents, leading to inconsistent findings 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Richardson et al reported that enterovirus-driven pancreatic inflammation stained with the enteroviral capsid antigen vp1 was identified in the 40% of type 2 diabetes patients, which was higher than the healthy non-diabetic control (13%) [21]. On the other hand, Gkrania-Klotsas et al reported that the prevalence of Coxsackievirus B neutralizing antibodies was not different between the type 2 diabetes patients and the subjects without diabetes [22]. In the type 2 diabetes patients of sub-Saharan African, positive human herpesvirus 8 DNA associated with lower insulin secretion and lower BMI comparing with the type 2 diabetes patients without human herpesvirus 8 infection [23].…”
Section: Discussionmentioning
confidence: 98%
“…Most individuals appear to become infected with CVB3 or closely related species at some point in their lives, 2,28,29 and systemic infection can be severe. [3][4][5] The contrast raised between comparatively rare reports of severe symptoms with a common infection suggests a non-uniform response to the virus.…”
Section: Discussionmentioning
confidence: 99%
“…1 A recent study based on seropositivity in diabetics estimates that up to 75% of people are seropositive to any given strain of coxsackievirus, 66% for CVB3 alone. 2 In contrast, severe symptoms are comparatively rare. In newborns, severe cases of viral hepatitis are periodically reported as a result of group B Coxsackieviruses, including CVB3.…”
Section: Introductionmentioning
confidence: 93%